Lifelong learning and the Roma minority in Central and Eastern Europe - Óhidy, Andrea; Forray, Katalin R. (Emerald Publishing Limited, 2019)
Access, attainment and success of Roma people in education are at a crisis point across Europe. Recent research has revealed that Roma people are the most underrepresented group in schools and other educational institutions. Policy makers across Central and Eastern Europe face the challenge of reversing the disadvantaged situation of the Roma minority. There is a whole host of policy strategies, measures and projects across Europe which offer similar solutions on national, regional and local levels. This book discusses the current educational climate and the impact of these policy measures for Roma people in eight Central and Eastern European countries: Bulgaria, Croatia, Czech Republic, Hungary, Moldova, Poland, Romania, and Slovakia. There is a severe lack of information about the Roma people in the public domain. This book seeks to raise awareness of this forgotten minority and evaluate the policies implemented to integrate the Roma people into the education system, using many different cultural perspectives written by experts across Central and Eastern Europe. This book will prove invaluable to those in the field of comparative education, educational leaders and practitioners in Central and Eastern Europe and beyond.
Includes index.
Keywords: Romanies -- Education -- Europe, Central.; Romanies -- Education -- Europe, Eastern.; Education, Adult & Continuing Education.; Adult education, continuous learning.; elektronické knihy; electronic books